Diversidade e estruturação genética em populações africanas e brasileiras de garça-vaqueira (Bubulcus ibis, Linnaeus,1758) determinadas por microssatélites - Geronimo, Cristiana Trujilu (2018)
Bubulcus ibis (cattle egret) is an ardeid whose original distribution included the countries of Africa, southern Europe and Western Asia. At the end of the 19th century, the species was first recorded in northern South America and by 1970 already spread across the continent. One of the hypotheses of the entry of this bird on the continent assumes transoceanic crossings from Center-West of the African continent to the regions of Suriname and Guyana, an from this area they had dispersed. The objective of this work was to study the process of colonization of Brazil by means of microsatellite markers. We analyzed 14 microsatellite DNA loci extracted from 300 blood samples (N = 134 Africans and N = 166 Brazilians) of twenty-two populations. Similar levels of genetic diversity were found in the African and Brazilian populations, but a greater diversity was observed in African populations. By Fst and AMOVA tests, significant differentiation was found between all individual and by the pairwise Fst analysis was evident that this differentiation is due more to differences between the Brazilian and African populations. Bayesian analysis of genetic groupings revealed a clear structuring between populations of the native and colonized area. The result of the Bayesian analysis indicates that the birds would leave the West African region, without indicating which region and they arrived mainly in the Brazilian Northeast / North regions (Pará, Pernambuco and Fernando de Noronha). Similar levels of genetic diversity among African and Brazilian populations and the absence of inbreeding in the Brazilian populations are consistent with the assumption that the colonization occurred with several inputs (propagules) and with a reasonable number of individuals. The low degree of structuring discards the occurrence of gene flow, previously assumed with mitochondrial data.